2023
DOI: 10.1186/s13068-023-02337-9
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable and high-level microbial production of plant hemoglobin in Corynebacterium glutamicum

Abstract: Background Plant hemoglobin shows great potential as a food additive to circumvent the controversy of using animal materials. Microbial fermentation with engineered microorganisms is considered as a promising strategy for sustainable production of hemoglobin. As an endotoxin-free and GRAS (generally regarded as safe) bacterium, Corynebacterium glutamicum is an attractive host for hemoglobin biosynthesis. Results Herein, C. glutamicum was engineered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Previous reports showed that bovine hemoglobin, deer mouse hemoglobin, and cowpea leghemoglobin II exhibited similar faster mobilities in SDS-PAGE ( Arredondo-Peter et al, 1997 ; Natarajan et al, 2011 ). A recent study observed LBA expressed intracellularly in C. glutamicum exhibiting a migration pattern on SDS-PAGE also below 15 kDa ( Wang et al, 2023 ). The results indicate that LBA exhibits a faster mobility in SDS-PAGE, which might be related to the conformation of LBA.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports showed that bovine hemoglobin, deer mouse hemoglobin, and cowpea leghemoglobin II exhibited similar faster mobilities in SDS-PAGE ( Arredondo-Peter et al, 1997 ; Natarajan et al, 2011 ). A recent study observed LBA expressed intracellularly in C. glutamicum exhibiting a migration pattern on SDS-PAGE also below 15 kDa ( Wang et al, 2023 ). The results indicate that LBA exhibits a faster mobility in SDS-PAGE, which might be related to the conformation of LBA.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the challenge of directly measuring intracellular expression levels of target proteins, many studies fused the coding sequence (CDS) of the target gene with a fluorescent protein CDS [ 6 , 22 , 37 ]. This approach allows the fluorescence values of the fusion protein to serve as an indirect reflection of the target protein's expression levels.…”
Section: Resultsmentioning
confidence: 99%
“…In the latest study, S‐Hb, maize‐Hb, rice‐Hb, and S. cerevisiae ‐Hb were successfully synthesized in Corynebacterium glutamicum . [ 62 ] Among them, the highest expression of S‐Hb, comprising 20% of the total protein, was achieved using a high‐throughput screening method based on the fusion of Hb with a green fluorescent protein. This method optimized the N‐terminal coding sequence of Hb genes, native inducible promoters, and plasmid copy number.…”
Section: Discussionmentioning
confidence: 99%
“…glutamicum , could reach 28% by adding 1 g L −1 ALA to the fermentation medium. [ 62 ] However, this heme‐binding ratio is still low, and this approach would increase the culture cost by over 60%. [ 16 ] Therefore, in this study, the rate‐limiting steps catalyzed by Hem2p, Hem3p, and Hem4p were eliminated using protein scaffolds, promoting the transport of their substrates (ALA, PBG, and HMB) and improving the heme titer (90.24%, Figure 4a ).…”
Section: Discussionmentioning
confidence: 99%